1999
DOI: 10.1073/pnas.96.10.5645
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 90 mediates macrophage activation by Taxol and bacterial lipopolysaccharide

Abstract: Taxol, a plant-derived antitumor agent, stabilizes microtubules. Taxol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
135
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(147 citation statements)
references
References 51 publications
11
135
1
Order By: Relevance
“…Hsp60 might signal through CD14, TLR-2 and TLR-4 [61,62], probably binding to a different molecule [63]. It was also suggested that Hsp90 and Hsp70 bound to LPS [64,65], and the latter could activate the innate immune response by a TLR4-mediated signal pathway [66]. In fish, beta-propiolactone (BPL) e inactivated VHSV was able to activate the expression of genes involved in the innate immune response in vitro [67], and some genes related to early immune response, such as IL-1b, TGF-b, IL-8 and iNOS, were simultaneously up-regulated in rainbow trout challenged with VHSV [68].…”
Section: Discussionmentioning
confidence: 99%
“…Hsp60 might signal through CD14, TLR-2 and TLR-4 [61,62], probably binding to a different molecule [63]. It was also suggested that Hsp90 and Hsp70 bound to LPS [64,65], and the latter could activate the innate immune response by a TLR4-mediated signal pathway [66]. In fish, beta-propiolactone (BPL) e inactivated VHSV was able to activate the expression of genes involved in the innate immune response in vitro [67], and some genes related to early immune response, such as IL-1b, TGF-b, IL-8 and iNOS, were simultaneously up-regulated in rainbow trout challenged with VHSV [68].…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of Raf-1 is also supported by the results showing that LPS-induced NO production was significantly inhibited in RAW cells transfected with the Raf-1 antisense oligonucleotide. Recently, Byrd et al (24) reported that HSP90 can bind LPS and mediates macrophage activation by LPS. However, the exact action of LPS on Raf-1/HSP90 complex has not yet been clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable that SA abrogates the Erk1/2 MAP kinase pathway through the loss of Raf-1 in LPS-stimulated RAW cells. Of particular interest are a series of recent reports implicating HSP90 and its associated proteins in signal transduction of macrophage activation (24,25). Raf-1 protein exists in native complexes with HSP90 that can be formed in vitro by reticulocyte lysate, and its catalytic domain is sufficient for HSP90 binding (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the other potential molecules that are likely to be recruited and participate in optimal signaling for gene expression, small G proteins (reviewed in Ref. 65), heat shock protein 90 (66), and others have been implicated in LPS-and/or Taxol-induced macrophage activation. The role of CD11b/CD18 might be analogous to that of CD14, where CD11b/CD18 functions to bind Taxol (via CD18) and LPS, whereas associated TLR4 molecules function as signal transducing receptors.…”
Section: Figurementioning
confidence: 99%